INFLUENCE OF GENDER AND COURSE STREAM ON EXAMINATION ANXIETY AMONG COLLEGES OF EDUCATION STUDENTS IN KWARA STATE, NIGERIA - Adio, AbdulGafar Alafara; Lasisi, Adekola Kamil (Counsenesia Indonesian Journal Of Guidance and Counseling, 2024)
This study explored the influence of gender and course stream on examination anxiety among Colleges of education students in Kwara State, Nigeria. The study was a descriptive survey design. The population for this study was all College of Education students in Kwara State which was 7,421 while the sample was 364 College of Education students drawn from the above population. Examination Anxiety Scale (EAS) was used to collect data from the respondents which was validated by five lecturers in the field of counselling psychology. Data collected were analyzed using percentages, mean and standard deviations, t-tests and analyses of Variance (ANOVA). The findings of this study show that the majority of college education students in Kwara State, Nigeria exhibited examination anxiety moderately (F=98, P= 81.9%). The findings revealed a significant difference in the examination anxiety among colleges of education students in Kwara State, Nigeria based on gender (t.cal.=11.96, p.<0.05). The findings also found no significant difference in the examination anxiety among colleges of education students in Kwara State, Nigeria based on course stream (F.cal=0.31, P.>0.05). The study concludes that the majority of college of education students experienced moderate examination anxiety; while male and female college of education students were deferred in their examination anxiety level. The study recommended among other things that; the counsellors should be holding counselling programme training on examination anxiety at least once a semester. It was also recommended that counsellors should always focus on all possible factors contributing to the prevalence of examination anxiety among female students without neglecting their male counterparts.